Overlapping turbulent boundary layers in an energetic coastal sea - Arnaud F. Valcarcel; Craig L. Stevens; Joanne M. O'Callaghan; Sutara H. Suanda (Ocean Science, 2025)
Turbulent mixing properties were directly observed to understand the interactions and overlapping events of wind-forced and tidally forced boundary layers in a deep, weakly stratified coastal sea. Te-Moana-o-Raukawa / Cook Strait of Aotearoa / New Zealand is an 𝒪(200 m) deep, energetic strait, known to experience both strong tidal currents and high wind speeds. More than 𝒪(40 000) quality-controlled turbulence observations were obtained from an ocean glider equipped with a microstructure profiler and a current speed through water sensor. Tidal flows of 𝒪(1 m s−1) and wind speeds of 𝒪(10 m s−1) independently enhanced turbulent dissipation to ϵ=O(10-5Wkg-1) in bottom and surface mixed layers. Over a 4 d period, boundary-generated turbulence was evident in the interior water column on 10 occasions, enhancing interior diapycnal diffusivity levels by 5–35-fold, reaching Kz=𝒪(0.1–1 m2 s−1). In three instances, the surface and bottom mixed layers overlapped. These overlapping boundary layers were present in water depths 5-fold deeper than previously observed, which has implications for the vertical extent of material fluxes from the surface or seafloor. Interior stratification was transient, emerging from far-field advection of low-density surface water, and supported by vertical buoyancy fluxes that were episodically eroded by boundary-generated turbulence. Combining observations with one-dimensional General Ocean Turbulence Model (GOTM) outputs, turbulence interactions in the interior were found to be modulated by wind, tides, and transient stratification fields, in turn influencing the vertical structure of sinks and sources of turbulent kinetic energy. Enhanced vertical transport toward the interior of the near-boundary shear-produced turbulence was found to erode interior stratification. The interplay between antecedent stratification, turbulence generation, and vertical transport allows boundary layers to interact and modulate the vertical structure of seawater properties in deep coastal passages.